Pengaruh kompetensi, pengalaman dan kelayakan guru terhadap pencapaian sekolah dalam subjek pengajian perniagaan tingkatan enam - Subramaniam, Kolandan (2021)
Education has a crucial role in developing human capital with strong identity, noble personality, vast knowledge, and high skills to meet the needs of a developed country. The achievement of a school involves its success in generating students who excel academically. Teachers’ competence is the foundation in the development of national education. The primary objective of this study is to measure teachers’ competence on school achievement in business studies across the Northern Zone of Peninsular Malaysia. This study assessed the role of teachers' competence, experience, and qualification in determining school achievement in business studies at the Form Six level. The quantitative data, retrieved from 155 teachers using survey questionnaire, were described descriptively in accordance to the study purpose - to identify teacher competencies. The selection of data analysis methods was based on the research questions. Inference statistical analysis, as well as correlation and regression tests, was performed to determine the correlations among the study variables. The data were analysed using SPSS, while the mediator effect was analysed using PROCESS analysis. The findings revealed the moderately significant correlation between teacher competence and school achievement, while teaching experience and teacher qualification emerged as insignificant mediators. Apparently, school achievement was based on the ability of teachers in mediating their competence to help students reach their potential. The study outcomes are in line with the Iceberg Competency Model, while simultaneously suggesting the need to identify other factors that contribute to school achievement. Essentially, this study highlights teacher competence as a significant factor to school achievement in business studies at the Form Six level within the context of Northern Zone of Peninsular Malaysia